"Is the Quarterback a 'Crip'?": The Presence of Gangs in Collegiate Athletics Programs. (December 2013) - Rojek, Jeff; Decker, Scott H.; Alpert, Geoffrey P.; Hansen, J. Andrew
Over the past 30 years, gangs have moved from large cities to suburban communities and small cities. Their presence has also been observed in public institutions such as secondary schools and the military. This study examines the presence of gang-involved individuals in another public institution, college athletics. While there are popular media reports of college athletes involved in gang activity, there has been no empirical research on the topic. The present study reports on the results from a national survey of athletic directors and campus police chiefs at universities with high-profile athletics programs, and interviews with student-athletes enrolled in two of these universities. The findings show the large majority of all three groups believe athletes affiliated with gangs are participating in college athletics. However, few athletic directors and campus police chiefs report the presence of gang-involved athletes on their own campus, and only a small number of athletes report that their teammates were also gang members. More research is needed to understand the scope and impact of this presence.